Comparing Quantitative Trait Loci and Gene Expression Data. (17th August 2008) - Han, Bing; Altman, Naomi S.; Mong, Jessica A.; Klein, Laura Cousino; Pfaff, Donald W.; Vandenbergh, David J.
Abstract : We develop methods to compare the positions of quantitative trait loci (QTL) with a set of genes selected by other methods, such as microarray experiments, from a sequenced genome. We apply our methods to QTL for addictive behavior in mouse, and a set of genes upregulated in a region of the brain associated with addictive behavior, the nucleus accumbens (NA). The association between the QTL and NA genes is not significantly stronger than expected by chance. However, chromosomes 2 and 16 do show strong associations suggesting that genes on these chromosomes might be associated with addictive behavior. The statistical methodology developed for this study can be applied to similar studies to assess the mutual information in microarray and QTL analyses.